Cervical malignant peripheral nerve sheath tumors: A case report and literature review - SUN Shuohui; LIU Qinyao; MA Junli; LI Xiao; WANG Zhifa (Kouqiang hemian waike zazhi)
Malignant peripheral nerve sheath tumor (MPNST) is a invasive malignant tumor originating from the differentiation of peripheral nerve trunks or nerve sheaths, which is extremely rare in clinical practice. This paper reports a case of MPNST of oral, maxillofacial and neck that recently admitted to our department. Combined with relevant literature reports at home and abroad in recent years, the growth pattern, prone site, clinical manifestations, histopathological features, imaging findings, as well as the thorougency of surgical resection in treatment and prognosis were discussed. As a kind of tumor with a high degree of malignancy, the recurrence rate of MPNST is determined by the design of surgical method, the size of resection, and whether to further radiotherapy and chemotherapy after surgery.